The analysis of algorithm for transmitters locating problem - Lazaravičius, Saulius; Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2023)
The analysis of ACO algorithm for transmitters locating problem is presented in this paper.
Keywords: combinatorial optimization; metaheuristic; ant colony optimization; ACO; transmitterslocating problem; set covering problem